A study on coverage and compliance of mass drug administration for lymphatic filariasis in Prayagraj District, Uttar Pradesh, India - Ram, Santraj; Prakash, Shiv; Singh, Richa; Prakash, Gyan; Anand, Deepak (International Journal Of Community Medicine And Public Health, 2021)
Background: Lymphatic filariasis is one of the six infectious diseases identified by the International Task Force for Disease Eradication as “eradicable” or “potentially eradicable. It is estimated that, to interrupt transmission of lymphatic filariasis, MDA compliance must exceed 65–75%. This study was conducted to assess coverage and compliance of mass drug administration for lymphatic filariasis in Prayagraj District. Methods: This was a pre-tested, questionnaire based cross-sectional study. The study subjects (508) were selected randomly from rural (clusters of three villages) and urban (cluster of one ward) area of Prayagraj, Uttar Pradesh. Data was analyzed by using software SPSS version 23.0 and Chi-square test was used to test the association between the different variables. p-value less than 0.05 was considered as significant. Results: The overall coverage rate, compliance rate, coverage-compliance gap and effective coverage rate of study population (eligible for MDA) in Prayagraj District were 69.94%, 84.19%, 15.81% and 58.88% respectively. The coverage rate and effective coverage rate were 78.71% and 64.85% respectively among urban area as well as 66.99% and 56.88% respectively among rural area. Conclusions: The coverage rate and effective coverage rate were higher among population in urban area as compared to rural area while compliance rate was lower and hence coverage-compliance gap was higher among population in urban area as compared to rural area. The most common reason for not consuming drugs was ‘drugs not delivered by drug distributors’ (73.11%).